Household drinking water quality and its predictors in flood-prone settings of Northwest Ethiopia: A cross-sectional community-based study. Issue 4 (April 2023) - Birhan, Tsegaye Adane; Bitew, Bikes Destaw; Dagne, Henok; Amare, Dagnachew Eyachew; Azanaw, Jember; Andualem, Zewudu; Dessie, Awrajaw; Guyasa, Gebisa; Getaneh, Alem; Addisu, Ayenew; Genet, Mengesha; Engdaw, Garedew Tadege; et al.
Abstract: Globally, the deterioration of drinking water quality is a major public health problem that contributes to the spread of disease and causes death. Therefore, it is important to have regular quality control monitoring. This study aimed to assess the level of physicochemical and bacteriological quality of household drinking water and its contributing factors in flood-prone settlements of South Gondar Zone, Ethiopia. A community-based cross-sectional study was conducted in flood-prone settings of Northwest Ethiopia from January 17 to March 30, 2021. Structured questionnaires were used to gather the sociodemographic, environmental, and behavioral data. A total of 675 drinking water samples were collected from water storage containers of selected households. Logistic regression models were used for both univariate and multivariable studies. The survey included a total of 675 households. The mean values of pH (5.9 ± 1.03), turbidity (6.7 ± 2.21 NTU), and free residual chlorine (0.02 ± 0.01 mg/l) did not meet the WHO recommended limits for drinking water. The prevalence of fecal contamination of drinking water in the study area was 62.2% with [95% CI (53–60%)]. Family size [AOR = 2.205, 95% CI (1.375–3.536), absence of latrine [AOR = 3.449, 95% CI (1.349–8.823)], and lack of a separate container to draw water from its storage [AOR = 0.454, 95% CI (0.249–0.827)] were significant predictors for fecal contamination of household drinking water. In conclusion, the water quality in terms of pH, turbidity, residual chlorine, and bacteriological parameters was poor and not suitable for consumption. High prevalence of fecal contamination of water was found, and it was significantly associated with family size, the absence of a latrine, and the lack of a separate cap to take water from the storage. Therefore, continuous chlorination and monitoring its concentration, educating the community on how to use stored water, educating the advantage of having a latrine, and promoting point-of-use treatments such as filtration and boiling are needed.